Factors Affecting Information System Management and Organizational Assessment Criteria related to Information System Management of Thai State Enterprises - Rodmorn, Chonnikarn; Porrawatpreyakorn, Nalinpat; Nuchitprasitchai, Siranee (Progress in Applied Science and Technology, 2019)
This research aimed at finding factors affecting IS/IT management and factors affecting organizational assessment criteria related to IS/IT management of Thai state enterprises. The sample group of this research was composed of 340 persons in 3 state enterprises. The data was collected through questionnaire. The statistical methods for this research were percentage, mean, standard deviation and multiple linear regressions. It was found that the support from executives, the management, the personnel competency, the communication and the participation affect IS/IT management and affecting organizational assessment criteria related to IS/IT management of Thai state enterprises at significant levels of 0.01 and 0.05. This can predict the IS/IT management of Thai state enterprises by 66.10% and the organizational assessment criteria related to IS/IT management of Thai state enterprises by 69.00%.